VERIFIKASI LOGAM TIMBAL PADA URIN DENGAN VARIASI ZAT PENGOKSIDASI DAN METODE DESTRUKSI BASAH PADA PEROKOK AKTIF - Mayaserli, Dyna Putri; Shinta, Dewi Yudiana (IAIN Batusangkar, 2019)
Lead (Pb) is heavy metal which is naturally found in the earth's crust or originates from human activities, for example from combustion gas emissions in motorized vehicle engines. Republic of Indonesia Ministry of Health Number 1406 / MENKES / SKI / IX / 2002 concerning the examination of lead levels in human biomarker specimens human measurements of lead levels in the human body can be carried out by blood, urine and hair specimens. The purpose of this study is to determine the levels of lead metal in the urine of active smokers. The results of research on lead levels obtained on accuracy parameters, namely the accuracy test results for the method of wet destruction using HNO3 has an average recovery of 71.8% while using HNO3 added H2SO4 has an average recovery of 46.48%, precision test results are obtained % RSD method of destruction on HNO3 was 28.80%. If on HNO3 added 50.58% H2SO4, linearity test (r) 0.999, LoD value on HNO3 0.76 and on LoD HNO3 H2SO4 added. Based on the results of the study of verification of lead metal using wet digestion in the urine of active smokers not in the range of acceptability conditions it indicates that the method cannot be valid for use in the examination of lead in urine by the method of wet destruction in the active smookers.